تشریعات الملکیة الفکریة فى حمایة البرمجیات فى الجمهوریة الیمنیة :دراسة میدانیة - د. فاطمة ابراهیم خمیس (المجلة الدولية لعلوم المكتبات والمعلومات)
This study deals with the legislation on intellectual property rights inthe Republic of Yemen, with a focus on the development of legislation toprotect software, and the position of the Republic of Yemen of internationalconventions relating to the protection of intellectual property rights .This,as well as to identify the types of software that guaranteed by the Yemenilaw protection, And pictures of the attack on the Rights of the author insoftware, And what are the penalties, In addition the paper try todetermining the bodies responsible for the protection of copyright . Thestudy also focus on the reality on the ground for violation of intellectualproperty rights in software in the Republic of Yemen, and what are thereasons for the deployment, and ways of combating it